Children Left Behind: Family, Refugees and Immigration in Postwar Europe. Issue 1 (12th August 2016) - Balint, Ruth
Abstract: In 1950, a welfare report by the IRO (International Refugee Organisation) in Austria recorded the particulars of Julia Alexenko, a displaced person, and her six-year-old daughter. Julia had been doing forced labour when her daughter was born, and the father had disappeared under the Soviets and not been heard from since. Now facing the imminent closure of the DP camps, she desperately sought asylum and resettlement in the West. But as the IRO medical report noted, her daughter, born prematurely, had severe physical and mental handicaps. Her file, and others like it, record the tragic dilemma faced by many families with disabled children whose applications for resettlement out of the DP camps in Occupied Europe between 1947 and 1952 were rejected by Western countries. Some, such as Julia Alexenko, refused to separate from their children, and were forced into an uncertain future in the local economy. But others, often under considerable pressure from the IRO, accepted offers of placement for their sick children in institutions in Belgium and Norway before leaving for countries like Australia. This article considers this hitherto hidden history in the light of new ideas about child welfare, humanitarianism and the family in the postwar era, which mostly assumed that keeping the family together was a priority at all costs; of older ideas about the segregation of the disabled; and of postwar immigration policies by western nations that sought to enforce ideas of population purity and health at the cost of the abandonment of disabled children by their families.